Strategi Guru dalam Pembentukan Pendidikan Karakter Melalui Kegiatan Program Pengabdian Masyarakat di MTs Pondok Pesantren Pancasila Kota Bengkulu - Afri Sukandar (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
This research is motivated by the importance of character education in preparing the nation's future successors. One place for improving morals and character formation is Islamic boarding schools, Islamic boarding schools have been present in Indonesian society since ancient times until now their existence still exists in the era of globalization which has been seen as endangering the existence of the Islamic religion in Indonesia, but there are still those who lack character and morals when still at home and even an alumnus. Of course, there are many Islamic boarding schools in Indonesia, each with its own characteristics in each region. However, the function and aim are the same, namely to shape the moral character of the students (santri). This research is intended to answer the problems: (1) What is the teacher's strategy in forming character education at MTs Pondok Pesantren Pancasila, Bengkulu City? (2) What are the obstacles in implementing the community service program at MTs Pancasila, Bengkulu City? (3) What are the characteristics of the students that are formed through the community service program activities? This type of research is qualitative research by collecting data using interviews, observation and documentation. The research carried out resulted in a final analysis, namely(1) The teacher's strategy in forming character education at MTs Pancasila Islamic Boarding School, Bengkulu City, one of which is by holding a community service program, namely a special program for third grade students to practice the knowledge they have acquired at MTs Pancasila Islamic Boarding School, Bengkulu City (2) Every activity or the program certainly has problems, the obstacles are that the implementing committee is still not very united and there is a lack of communication between one another and the students are still playing games when taking part in these activities (3) The character that is formed as a result of this community service program is social care. , independent, religious, creative, hard working and responsible, independent. Keyword: Strategi, Pendidikan Karakter, Pengabdian Masyarakat, Pesantren Pancasila